The symbolic construction of literary naming at the crossroads of tradition and modernity: towards new historicism in Ahmed Abodehman’s memoir The Belt - Ali M. Alshhre (Cogent Arts & Humanities)
Modern Saudi Arabian literature is a dynamic reproduction of the country’s ongoing socio-political transformations and cultural struggles. As writers negotiate the complexities of identity at the crossroads of tradition and modernity in a rapidly changing society, the role of literary motifs, such as names, becomes increasingly significant. This study, anchored within a new historicist perspective, explores the function of names in Ahmed Abodehman’s memoir The Belt. It illuminates the construction of literary naming and its role in the confluence of individual identity and collective cultural discourse within Saudi Arabia’s socio-cultural change through the character of Hizam. This analysis underscores the use of names as a nuanced literary device that imbues the narrative with deep cultural and ideological resonances. The study also highlights the cultural shifts evident in modern Saudi literature that are instrumental in exploring the evolving cultural topography of the nation. It further hammers on the complexities involved in the ‘triangular’ process of literary translation that the narrative has undergone, offering a critical perspective on the intricate interplay between cultural identity, linguistic diversity, and the dynamics of representation.